Paddle whispers - Wood, Douglas, 1951- (University of Minnesota Press, 1993)
Through poetic text and drawings, woven gracefully with quotes by John Muir, Walking Buffalo, Sigurd F. Olson, Henry David Thoreau, and others, Douglas Wood traces a journey by paddle and canoe that renews the spirit.